A high-performance, flexible and robust metal nanotrough-embedded transparent conducting film for wearable touch screen panels. Issue 7 (1st February 2016) - Im, Hyeon-Gyun; An, Byeong Wan; Jin, Jungho; Jang, Junho; Park, Young-Geun; Park, Jang-Ung; Bae, Byeong-Soo
Abstract : A junction resistance-free continuous metal nanotrough-embedded transparent conducting electrode (TCE) composite film (metal nanotrough-GFRHybrimer film) is reported. Abstract : We report a high-performance, flexible and robust metal nanotrough-embedded transparent conducting hybrid film (metal nanotrough-GFRHybrimer). Using an electro-spun polymer nanofiber web as a template and vacuum-deposited gold as a conductor, a junction resistance-free continuous metal nanotrough network is formed. Subsequently, the metal nanotrough is embedded on the surface of a glass-fabric reinforced composite substrate (GFRHybrimer). The monolithic composite structure of our transparent conducting film allows simultaneously high thermal stability (24 h at 250 °C in air), a smooth surface topography ( R rms < 1 nm) and excellent opto-electrical properties. A flexible touch screen panel (TSP) is fabricated using the transparent conducting films. The flexible TSP device stably operates on the back of a human hand and on a wristband.